The rise of the Greek aristocratic banquet - Węcowski, Marek 1969- (Oxford University Press, 2014)
Wecowski offers a comprehensive account of the origins of the symposion and its close relationship with the rise of the Greek city-state or polis. Held by Greek aristocrats from Homer to Alexander the Great, its distinctive feature was the importance of diverse cultural competitions among the guests